O USO DA ROBÓTICA NO ENSINO DE LÓGICA COMPUTACIONAL: UMA PROPOSTA PARA AS SÉRIES INICIAIS: THE USE OF ROBOTICS ON THE TEACHING OF COMPUTATIONAL LOGIC: A PROPOSAL TO THE BEGINNING GRADES (Revista Contexto & Educação, 2021)
The Internet of Things is a strong tendency in the contemporary and technological society. That said, the knowledge of computation concepts becomes a requisite to qualify citizens to the concept of the society of information. The stimulus of the logic-abstract thinking by means of processing and problem solving, while approaching the Computational Thinking concept, are essential paths to reach said goal. Thus, the present work describes a research that manufactured a robotic device and developed a mobile application utilizing the Arduino microcontroller and the AppInventor software, associated to a didactic sequence to introduce concepts of Computational Thinking. The main goal by utilizing those devices was to verify its unrolling alongside children in literacy age, by adopting the educational methodology of the educational robotics by the means of mobile devices. During its realization, it was possible to observe signs that the children that participated were able to reasonably deal with abstract questions as from this work’s proposed activities. It was also possible to conclude that actions like this demonstrate that the insertion of the Computational Thinking associated with ludic activities since the first scholar years is conceivable.
Keywords: Computational Thinking; Educational Technology; Robotics in Education